2019
DOI: 10.1007/978-981-13-9913-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Astroglia

Abstract: Astrocytes are principal cells responsible for maintaining the brain homeostasis. Additionally, these glial cells are also involved in homocellular (astrocyte-astrocyte) and heterocellular (astrocyte-other cell types) signalling and metabolism. These astroglial functions require an expression of the assortment of molecules, be that transporters or pumps, to maintain ion concentration gradients across the plasmalemma and the membrane of the endoplasmic reticulum. Astrocytes sense and balance their neurochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
344
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 254 publications
(353 citation statements)
references
References 445 publications
(462 reference statements)
9
344
0
Order By: Relevance
“…Astrocytes are morphologically and functionally heterogeneous cells primarily responsible for homeostasis of the CNS. These functions were recently reviewed [51], and include regulation of synaptic formation, control of connectivity of synapses, integration and synchronization of neuronal networks and the maintenance of BBB integrity [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. Importantly, astrocytes are also the fundamental defensive elements of the nervous tissue; insults to the brain or spinal cord trigger reactive astrogliosis, which spatially contains damaged area, while also facilitating postdamage regeneration of neural tissue [54,62,64]; in certain context astrogliosis can be maladaptive and neurotoxic [71].…”
Section: Adrenergic Astroglial Excitation and Neurodegenerationmentioning
confidence: 99%
“…Astrocytes are morphologically and functionally heterogeneous cells primarily responsible for homeostasis of the CNS. These functions were recently reviewed [51], and include regulation of synaptic formation, control of connectivity of synapses, integration and synchronization of neuronal networks and the maintenance of BBB integrity [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. Importantly, astrocytes are also the fundamental defensive elements of the nervous tissue; insults to the brain or spinal cord trigger reactive astrogliosis, which spatially contains damaged area, while also facilitating postdamage regeneration of neural tissue [54,62,64]; in certain context astrogliosis can be maladaptive and neurotoxic [71].…”
Section: Adrenergic Astroglial Excitation and Neurodegenerationmentioning
confidence: 99%
“…Nevertheless, the present iGlu u -based postulate of non-saturating Glu uptake for ITand PT-type corticostriatal synapses will need further verification under a wider range of conditions. It was already shown that the state of astrocytes could affect the structural plasticity of PAPs (Theodosis et al, 2008;Reichenbach et al, 2010;Bernardinelli et al, 2014;Heller and Rusakov, 2015;Verkhratsky and Nedergaard, 2018). Activity-and diseasedependent PAP retraction could produce a large variety of spill-out and spill-in effects which may not only change the access of the available transmitter(s) to respective neuronal and glial receptors, but also influence the efficacy of the astrocytic transport machinery itself (Armbruster et al, 2016).…”
Section: The Hypothesis Of Non-saturating Glu Uptake In Healthy Glutamentioning
confidence: 99%
“…The observations that glial cells change very early during neuropathology (Rodríguez et al, 2014;Verkhratsky et al, 2016) led to hypothesize that an insufficient homeostatic support to other cells in the CNS may be among the primary events which predispose neurons to dysfunction (Verkhratsky et al, 2016(Verkhratsky et al, , 2019. In this context, we have proposed that deregulation of astroglial Ca 2+ signalling, downstream of CaN, may contribute to this homeostatic failure (Lim et al, 2014(Lim et al, , 2016b.…”
Section: Conclusion: Is Astro-can a Master-regulator Of Homeostasis Imentioning
confidence: 99%